2016
DOI: 10.1590/2317-1782/20162015111
|View full text |Cite
|
Sign up to set email alerts
|

Autoavaliação e prontidão para mudança em pacientes disfônicos

Abstract: RESUMO Objetivo Analisar se existe associação entre a autoavaliação vocal e a prontidão para mudança em pacientes disfônicos. Método Participaram 151 pacientes com queixa vocal e diagnóstico de disfonia, entre 18 e 65 anos de idade, 47 homens e 104 mulheres, atendidos no ambulatório de voz de uma instituição pública. Foram aplicados quatro instrumentos de autoavaliação, incluindo o Questionário de Qualidade de Vida em Voz (QVV), o Índice de Desvantagem Vocal (IDV) e a Escala de Sintomas Vocais (ESV), além da u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 21 publications
1
11
0
1
Order By: Relevance
“…At the onset of treatment, the majority of the participants were at the contemplation stage, which agrees with previous studies that have used a single application of the URICA-VOICE scale [16-18]. It is possible that patients in the contemplation stage may not have noticed the need to change their voice behavior, resulting in a lack of perception regarding their voice problem.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…At the onset of treatment, the majority of the participants were at the contemplation stage, which agrees with previous studies that have used a single application of the URICA-VOICE scale [16-18]. It is possible that patients in the contemplation stage may not have noticed the need to change their voice behavior, resulting in a lack of perception regarding their voice problem.…”
Section: Discussionsupporting
confidence: 85%
“…At the end of the intervention, it was possible to observe that perception of improvement in voice production may contribute to patients’ self-esteem and motivate them to actively take part in rehabilitation [18, 23]. This is a positive factor that might have contributed to the greater motivation of the participants in the present study.…”
Section: Discussionmentioning
confidence: 88%
“…Similar results were found by a study (14) that found that most of the individuals were between the pre-contemplation and contemplation phases, and could not assume attitudes to face their problem. It is possible that these individuals arrived at the clinic at this stage because they were referred to the vocal therapy by their doctor, unaware of the cause of their vocal alteration and oblivious of the need to change their voice-related behavior (13) .…”
Section: Discussionmentioning
confidence: 99%
“…This study suggested the existence of an association between the other instruments of vocal self-assessment and the motivation for vocal therapy. Patients who presented worse voice related quality of life, greater voice disadvantage and a larger frequency of vocal symptoms were at the most advanced motivational stages for vocal therapy (13) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation